Sanksi Pidana Penjara Bagi Anak yang Melakukan Tindak Pidana Pembunuhan Dalam Perspektif Ultimum Remedium - Rizaldi Tri Pamungkas (Faculty of Law, Universitas Airlangga, 2022)
Abstract Based on the provisions of Article 2 letter I of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, namely deprivation of independence and sentencing as a last resort. In every judicial process, children have the right not to be arrested, detained, or imprisoned, except as a last resort and in the shortest time as stated in Article 3 letter g of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. The makers of the Juvenile Criminal Justice System Act regarding crimes and actions that there is no obligation for judges to impose criminal penalties and the first thing that can be sentenced is action. Judging from the order of imprisonment is the last order, namely the last one mentioned. However. in practice there are still children who are decided by the judge with imprisonment. In Law No. 11 of 2012 concerning the Juvenile Criminal Justice System, it is not clear that the limitations related to the imposition of imprisonment on children are not clearly regulated. Keywords: Imprisonment; Children in Conflict with the Law; Murder; Ultimum Remedium. Abstrak Berdasarkan ketentuan Pasal 2 huruf I Undang-undang Nomor 11 tahun 2012 tentang Sistem Peradilan Pidana Anak yaitu perampasan kemerdekaan dan pemidanaan sebagai upaya terakhir. Dalam setiap proses peradilan, Anak berhak untuk tidak ditangkap, ditahan, atau dipenjara, kecuali sebagai upaya terakhir dan dalam waktu yang paling singkat sebagaimana bunyi Pasal 3 huruf g Undang-undang Nomor 11 tahun 2012 tentang Sistem Peradilan Pidana Anak. Para pembentuk Undang-undang Sistem Peradilan Pidana Anak merumuskan tentang pidana dan tindakan bahwa memang tidak ada kewajiban Hakim untuk menjatuhkan pidana dan yang bisa dijatuhi adalah pertama itu tindakan. Dilihat dari urutannya pidana penjara merupakan urutan yang paling akhir yaitu yang paling belakang disebutkan. Namun. dalam prakteknya masih ada anak yang diputus oleh Hakim dengan pidana penjara. Dalam Undang-undang Nomor 11 tahun 2012 tentang Sistem Peradilan Pidana Anak tidak diatur jelas batasan-batasan terkait penjatuhan pidana penjara. Kata Kunci: Sanksi Pidana Penjara; Anak yang Berkonflik dengan Hukum; Tindak Pidana Pembunuhan; Ultimum Remedium.